Reorganisation and Merger of Schools at the Elementary level in Jharkhand Views of Stakeholders - Mohalik, Ramakanta (JOURNAL OF INDIAN EDUCATION, 2021)
The objective of this paper is to study the views of different stakeholders such as students, parents, teachers, Headmaster1 is used to address a persion of any gender who holds the head position in a school. Headmaster (HM) and education officers regarding problems and issues of reorganisation and merger of schools. Survey method was used with the help of Focused Group Discussion (FGD) and interview. Sample of 31 merged schools, 310 students, 74 parents, 54 teachers, and 31 HMs were selected by using multistage sampling from Jharkhand.FGD for students of merged school, interview for parents, teachers, HMs and education officers were used as tool for data collection. The collected data was processed in Excel and analysed by percent and words. The study found that— i) Majority of students did not feel good when the school got closed as they were very much attached with old school and it was near to their habitation. They have difficulty to go new school regularly. ii) Seventy-three percent of parents expressed that they felt unhappy about merger of old school as it was near and children come to school on their own. Now, parents are dropping and picking their wards from new school, which is hampering their daily work. iii) Sixty-three percent of teachers feel good as the present school was in the same campus. Old school had fewer classrooms, single teacher and it was difficult to manage all activities.